Memanfaatkan Literasi Digital Pada Anak Usia Dini Langkah Awal Menuju Generasi Cerdas Digital - Faiz Masruri; Abdul Hamid (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Utilizing digital literacy in early childhood is an important first step in forming a digitally intelligent generation in the future. Digital literacy does not only focus on the ability to use technology, but also on developing critical thinking skills, creativity, and the ability to communicate through digital media. In this digital era, children need to be equipped with a good understanding of how to use technology wisely and safely. Through digital media, children can learn in an interactive and fun way, which encourages them to be more active in exploring knowledge. However, it is important to note that technology must be used with proper supervision from parents and educators, so that children can make positive use of technology. Educators and parents must create an environment that supports the development of children's digital literacy by providing access to quality and relevant educational materials. With this, children will be ready to face the challenges of increasingly advanced times and can utilize technology to support their cognitive and emotional development in a balanced way. Digital literacy is a solid foundation for future generations who are more adaptive and ready to compete in the digital world